Tajemnice mądrości: uprawdopodobnienie związków pomiędzy literaturą mądrościową starożytnego Egiptu a neoplatońską filozofią polityczną - Zhang-Czabanowski, Wojciech Wilhelm (Humaniora. Czasopismo Internetowe, 2025)
The aim of this article is to examine whether there are connections between the wisdom literature of Ancient Egypt and Neoplatonic political philosophy. Using the definitione of political philosophy proposed by Dominic O’Meara, I try to show that Egyptian texts meet this definition. I then compare Neoplatonic political philosophy and Egyptian wisdom literature, showing similarities and common elements. In the rest of the article, I hypothesize that common threads with Egyptian texts may depend on Egyptian thought. At the end of the article I conclude that the fact that Plotinus’ teacher was Ammonius Saccas may explain this.